The innovator's toolkit : 50+ techniques for predictable and sustainable organic growth - Silverstein, David, 1965-; Samuel, Philip; DeCarlo, Neil (John Wiley & Sons, Inc., 2012)
"A compendium of tools and techniques that every innovator needs. The Innovator's Toolkit is an essential companion for every innovator, innovation team leader, operations manager, and corporate change agent who needs to drive organic growth. Written and presented in an easy-to-use reference format, the book helps users understand why, when, and how to apply each technique for maximum benefits and results. The fifty-plus tools and techniques in this book are organized around a framework for identifying innovation opportunities, generating new and unusual ideas, selecting the best ideas for further refinement, and implementing new solutions that better meet customer expectations. * This revised second edition includes significant updates to nearly two dozen techniques * Also offers several brand new techniques, including Idea Harvesting and Treatment, Seventy-six Standard Solutions, and Six Thinking Hats. This updated and revised edition of The Innovator's Toolkit simply helps innovation leaders, managers, and specialists do their jobs better than ever before---giving them more confidence, greatly reducing the chance of expensive failures, and packing more practical innovation knowhow under one cover than ever before"--Provided by publisher
Previous edition: 2009.
Keywords: Technological innovations -- Management.; Creative ability in business.; Business planning.; Project management.; elektronické knihy; electronic books